The Arabidopsis Cdk1/Cdk2 homolog CDKA;1 controls chromosome axis assembly during plant meiosis. (26th September 2019) - Yang, Chao; Sofroni, Kostika; Wijnker, Erik; Hamamura, Yuki; Carstens, Lena; Harashima, Hirofumi; Stolze, Sara Christina; Vezon, Daniel; Chelysheva, Liudmila; Orban‐Nemeth, Zsuzsanna; Pochon, Gaëtan; Nakagami, Hirofumi; et al.
Abstract: Meiosis is key to sexual reproduction and genetic diversity. Here, we show that the Arabidopsis cyclin‐dependent kinase Cdk1/Cdk2 homolog CDKA;1 is an important regulator of meiosis needed for several aspects of meiosis such as chromosome synapsis. We identify the chromosome axis protein ASYNAPTIC 1 (ASY1), the Arabidopsis homolog of Hop1 (homolog pairing 1), essential for synaptonemal complex formation, as a target of CDKA;1. The phosphorylation of ASY1 is required for its recruitment to the chromosome axis via ASYNAPTIC 3 (ASY3), the Arabidopsis reductional division 1 (Red1) homolog, counteracting the disassembly activity of the AAA + ATPase PACHYTENE CHECKPOINT 2 (PCH2). Furthermore, we have identified the closure motif in ASY1, typical for HORMA domain proteins, and provide evidence that the phosphorylation of ASY1 regulates the putative self‐polymerization of ASY1 along the chromosome axis. Hence, the phosphorylation of ASY1 by CDKA;1 appears to be a two‐pronged mechanism to initiate chromosome axis formation in meiosis. Synopsis: CDKA;1, the central cell cycle regulator in Arabidopsis and homolog of human Cdk1 and Cdk2, is essential for meiosis and especially needed for regulation of chromosome synapsis. In early meiosis, CDKA;1 promotes chromosome axis assembly via ASY1 phosphorylation. CDKA;1 and HORMA domain protein ASY1 co‐localize on meiotic chromosomes, being released upon chromosome synapsis. ASY1 is phosphorylated by CDKA;1 in early meiosis. ASY1 phosphorylation antagonizes the releasing force of PCH2 ATPase, thereby enabling ASY1 localization on chromosomes in early meiosis. PCH2 is required for the efficient nuclear targeting of ASY1 in early meiosis. Abstract : Phosphorylation of the HORMA domain protein ASY1 by the central cell cycle kinase promotes its recruitment onto meiotic chromosomes both via protein interactions and by countering disassembly ATPase PCH2.